Seasonal acclimation of preferred body temperatures improves the opportunity for thermoregulation in newts - Hadamová, Markéta; Gvoždík, Lumír (Physiological and biochemical zoology, 2011)
Seasonal acclimation and thermoregulation represent major components of complex thermal strategies by which ectotherms cope with the heterogeneity of their thermal environment. Some ectotherms possess the acclimatory capacity to shift seasonally their thermoregulatory behavior, but the frequent use of constant acclimation temperatures during experiments and the lack of information about thermal heterogeneity in the field obscures the ecological relevance of this plastic response. We examined the experimentally induced seasonal acclimation of preferred body temperatures (T(p)) in alpine newts Ichthyosaura (formerly Triturus) alpestris subjected to a gradual increase in acclimation temperature from 5°C during the winter to a constant 15°C or diel fluctuations between 10° and 20°C during the spring/summer. Both the mean and range of T(p) followed the increase in mean acclimation temperature without the influence of diel temperature fluctuations. The direction and magnitude of this acclimatory capacity has the potential to increase the time window available for thermoregulation. Although thermoregulation and thermal acclimation are often considered as separate but coadapted adjustments to thermal heterogeneity, their combined response is employed by newts to tackle seasonal variation in a thermoregulatory-challenging aquatic environment.
Keywords: Behavior, Animal; chování zvířat; Body Temperature Regulation; Temperature; teplota; termoregulace; Animals; Salamandridae; roční období; Seasons; zvířata; aklimatizace; Acclimatization